ANALYSIS OF STRATEGIES TO IMPROVE THE EFFECTIVENESS OF PROTOCOL AND EXECUTIVE COMMUNICATION FUNCTIONS AT THE REGIONAL SECRETARIAT OF BANDAR LAMPUNG CITY - Muhammad Ceasar Aldafa; Agus Purnomo (International Journal of Multidisciplinary Reseach, 2026)
The research method used is descriptive qualitative research. This method is used to describe the analysis of strategies to improve the effectiveness of protocol and leadership communication functions at the Bandar Lampung City Regional Secretariat. All data were obtained directly from informants in the field using interviews and document studies. The results of the study indicate that, based on the five dimensions of organizational effectiveness, it can be concluded that improving the effectiveness of protocol and leadership communication functions at the Bandar Lampung City Regional Secretariat requires a comprehensive and integrated approach. Clarity of objectives, availability and management of resources, effectiveness of internal processes, adaptability to the environment, and strengthening of organizational values ​​and culture are key interrelated factors.